2020
DOI: 10.1177/0023677220922573
|View full text |Cite
|
Sign up to set email alerts
|

Application of the 3R principles: Vertebrae as an additional source of murine bone-marrow cells

Abstract: Experimental murine models are an essential tool in the field of bone marrow (BM) transplantation research. Therefore, numerous mice are required to obtain a sufficient number of BM cells, which is in contrast with the Reduction principle of the 3R principles. The selection of the cell source and the isolation protocol are therefore critical in obtaining a sufficient yield of cells for experiments. Nowadays, the vertebrae are already used as an extra source of BM cells to enrich the number of isolated cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Ultimately, alternatives to isolation of cells from and experiments with laboratory animals are needed to reduce the number of animals sacrificed for research. Thus, establishing new cell lines supports the 3R guidelines ( 24 ) and will help to achieve the future aim of ending the use of animals in research in the USA and the European Union ( 67 ). This new MC model will therefore sustain future studies on mechanisms and pharmacologic intervention of MC activation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Ultimately, alternatives to isolation of cells from and experiments with laboratory animals are needed to reduce the number of animals sacrificed for research. Thus, establishing new cell lines supports the 3R guidelines ( 24 ) and will help to achieve the future aim of ending the use of animals in research in the USA and the European Union ( 67 ). This new MC model will therefore sustain future studies on mechanisms and pharmacologic intervention of MC activation.…”
Section: Discussionmentioning
confidence: 82%
“…Challenging about PMCs is, however, that peritoneal lavages often yield only strictly limited amounts of enriched PMCs that cannot be cultured over a longer time period. As a consequence, to extensively characterize PMC biology, plenty of mice need to be sacrificed to yield validated scientific data, which is not in agreement with the 3R principles of animal welfare ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, alternatives to isolation of cells from and experiments with laboratory animals are needed to reduce the number of animals sacrificed for research. Thus, establishing new cell lines supports the 3R guidelines (24) and will help to achieve the future aim of ending the use of animals in research in the USA and the European Union (67). This new MC model will therefore sustain future studies on mechanisms and pharmacologic intervention of MC activation.…”
Section: Discussionmentioning
confidence: 88%
“…The copyright holder for this preprint this version posted January 24, 2023. ; https://doi.org/10.1101/2023.01. 24.525344 doi: bioRxiv preprint and Arf was not detectable in PMC-306 cells. We demonstrated that these aberrations lead to an enhanced cell cycle activity, a strongly increased proliferative capacity and best explains the mechanism of PMC transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation